ANALYSING LEVELS OF FLAVONOID, SAPONIN, AND TANNIN OF MANGO (Mangifera indica L.) PEEL WASTE AS AN ANTIBACTERIAL AGENT AGAINST Escherichia coli - Alya Faiza; Rais Nur Latifah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Escherichia coli bacteria are a microorganism that is needed in the digestive system, but if the amount is excessive, it will be pathogenic and cause diseases, including diarrhea. Antibacterial can be used as an inhibitor of the development of microorganisms that are capable of causing disease and death. The focus of this study is to identify the phytochemical compounds contained in it, as well as how the bark of mango arumanis has antibacterial properties that fight Escherichia coli by using soxhletation extraction methods, uv-vis spectrophotometry, gravimetry, titrimetry and disc diffusion. The results showed that ethanol extract of mango arumanis peel contains flavonoids, saponins, alkaloids, and tannins with a flavonoid content of 2.27%; saponin 51.63%; and tannins 3.2553%. The antibacterial activity of Escherichia coli in the category is quite effective with a concentration of 46%.